English Oral and Written Receptive Skills of Vocational Lecturers - Hartani, Tuti; Sulindra, Eric; Tedjo, Ester Widawati; Teopilus, Susana (Journal of Education Reseach and Evaluation, 2022)
Reading and listening as receptive skills have been investigated from multiple angles. The current research is a descriptive study aiming to find the correlation between the two receptive skills. In addition, it investigates the strengths and weaknesses in terms of four subskills (finding the main idea, answering stated-detail questions, answering implied-detail questions, and identifying the meaning of the expressions used in an oral or written discourse) performed by the respondents who were grouped as the high achievers and the low achievers. The research findings confirmed a significantly positive correlation between reading and listening skills. In the listening test, the high achievers had strengths in all of the subskills, whereas the low achievers’ performance in all the subskills was below 50%, which implied that they had weaknesses in all of the listening subskills. In the reading test, the high achievers had strengths in all subskills. The low achievers showed strong reading performance in the subskills of finding main ideas and answering stated-detail questions. At the same time, they had weaknesses in the subskills of answering implied-detail questions and identifying the meaning of the expressions used in the written discourse. This result implies that vocabulary is the most important factor to upgrade to anticipate the weakness in the subskills of answering implied-detail questions and identifying the meaning of the expressions used in the written discourse.